A study on solar energy as an alternative power supply for conventional electricity during Malaysia’s Covid-19 Movement Control Order (MCO): the public perception / Nurhidayah Samsul Rijal ... [et al.] - Samsul Rijal, Nurhidayah; Ahmad, Nur Azfahani; Abd Rased, An nisha Nur Welliana; Zulkernain, Muhammad Zahir (2021)
In January 2020, the World Health Organization (WHO) proclaimed the emergence of a new coronavirus pandemic, COVID-19. During this unprecedented time, the Movement Control Order (MCO) enforcement was implemented in Malaysia for 3 months (March – May) to control social distancing which would correspondingly help in reducing the virus transmission. During this period, all business premises and institutions were commanded to remain closed. Furthermore, all the citizens were strictly advised to remain in their respective households. This enforcement unfortunately, resulted in high monthly electricity bills since they were required to stay in the house all the time. Hence, it impacted the overall gross income of consumers and has sparked dissatisfaction as well as frustration among them. Therefore, an initiative is needed to help overcome this issue. Solar-generated electricity is therefore perceived as a significant initiative for reducing the consumption energy from Tenaga Nasional Berhad (TNB) grid. This survey has identified the changes in electricity bills for 5 months as a result of MCO enforcement. Thus, this research aims to identify the level of perception among respondents regarding solar energy as an alternative to reduce electricity bills and the challenges in applying this technology specifically for four (4) residentials areas in Seri Iskandar, Perak. The stratified random sampling method was chosen to conduct this survey which depended on the total of population in these four areas. This research intends to be useful in promoting the effectiveness and sustainability of solar energy technology among the public.